Antimicrobial, antioxidant and anticancer activities of Laurencia catarinensis, Laurencia majuscula and Padina pavonica extracts - Nouf M. Al-Enazi; Amani S. Awaad; Mohamed E. Zain; Saleh I. Alqasoumi (Elsevier, 2018)
The antimicrobial, antioxidant, and anticancer activities of ethanolic extract of Laurencia catarinensis, L. majuscula and Padina pavonica were determined. The highest antibacterial activity; 23.40 ± 0.58 mm (00.98 µg/ml) and 22.60 ± 2.10 mm (03.90 µg/ml) were obtained against Klebsiella pneumonia by Laurencia catarinensis and Padina pavonica, respectively. However, Padina pavonica showed excellent antibacterial activity against Bacillus subtilis (21.7 ± 1.5 mm; 1.95 µg/ml), Staphylococcus aureus (21.7 ± 0.58 mm; 1.95 µg/ml), Streptococcus pyogenes (20.7 ± 1.2 mm; 1.95 µg/ml) and Acinetobacter baumannii (20.1 ± 1.2 mm; 3.9 µg/ml). Moreover, the highest antifungal activity; 24.7 ± 2.0 mm (0.98 µg/ml), 23.7 ± 1.5 mm (0.98 µg/ml), 23.6 ± 1.5 mm (0.98 µg/ml) was obtained by Padina pavonica against Candida tropicalis, C. albicans and Aspergillus fumigatus, respectively. The algal extracts showed DPPH radical scavenging activity in a concentration-dependent manner with maximum scavenging activity (77.6%, IC50 = 5.59 µg/ml and 77.07%, IC50 = 14.3 µg/ml) was provided by Padina pavonica and Laurenica majuscula, respectively. The in vitro antitumor activity revealed that the IC50 values of Padina pavonica were 58.9, 115.0, 54.5, 59.0, 101.0, 101.0, and 97.6 µg/ml; Laurencia catarinensis were 55.2, 96.8, 104.0, 78.7, 117.0, 217.0, 169.0 µg/ml; and Laurencia. majuscula were 115.0, 221.0, 225.0, 200.0, 338.0, 242.0, and 189.0 µg/ml; respectively against A-549 (Lung carcinoma), Caco-2 (Intestinal carcinoma), HCT-116 (Colon carcinoma), Hela (Cervical carcinoma), HEp-2 (Larynx carcinoma), HepG-2 (Hepatocellular carcinoma), and MCF-7 (Breast carcinoma) cell lines. Keywords: HCT-116 (Colon carcinoma), Hela (Cervical carcinoma), HEp-2 (Larynx carcinoma), HepG-2 (Hepatocellular carcinoma), MCF-7 (Breast carcinoma), Acinetobacter baumannii, Bacillus subtilis